1980
DOI: 10.1017/s0022112080000870
|View full text |Cite
|
Sign up to set email alerts
|

A strong interaction theory for the creeping motion of a sphere between plane parallel boundaries. Part 1. Perpendicular motion

Abstract: This paper presents the first ‘exact’ solutions to the creeping-flow equations for the transverse motion of a sphere of arbitrary size and position between two plane parallel walls. Previous solutions to this classical Stokes flow problem (Ho & Leal 1974) were limited to a sphere whose diameter is small compared with the distance of the closest approach to either boundary. The accuracy and convergence of the present method of solution are tested by detailed comparison with the exact bipolar co-ordinate sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
126
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(135 citation statements)
references
References 11 publications
9
126
0
Order By: Relevance
“…Our analysis in Part 1 for particle motion in a quiescent fluid shows that in certain cases the behavior in 2-D and 3-D cases was very similar, whereas in other cases there were qualitative differences. Here, we compare our results to those of Bungay and Brenner [9, 10] for a spherical particle in a circular tube in Poiseuille flow, and of Refs [11][12][13] for a spherical particle between two plane parallel boundaries in Poiseuille and Couette flows. The results in these papers are presented in different forms than the results of the present paper, so some additional calculations were required to rescale the variables.…”
Section: Discussionmentioning
confidence: 77%
“…Our analysis in Part 1 for particle motion in a quiescent fluid shows that in certain cases the behavior in 2-D and 3-D cases was very similar, whereas in other cases there were qualitative differences. Here, we compare our results to those of Bungay and Brenner [9, 10] for a spherical particle in a circular tube in Poiseuille flow, and of Refs [11][12][13] for a spherical particle between two plane parallel boundaries in Poiseuille and Couette flows. The results in these papers are presented in different forms than the results of the present paper, so some additional calculations were required to rescale the variables.…”
Section: Discussionmentioning
confidence: 77%
“…From here on, without loss of generality, we shall restrict our attention to the "11" and "12" functions. (Ganatos, Pfeffer and Weinbaum 1978), the motion of a sphere between two parallel infinite plates (Ganatos, Pfeffer and Weinbaum 1980) and the sedimentation of a sphere in an inciined channel (Ganatos, Weinbaum and Pfeffer 1982). For our two-sphere problem, a suitable co-ordinate system exists.…”
Section: ;mentioning
confidence: 99%
“…The authors reported good agreement with analytical solutions [4,5] for a train of spherical particles in axisymmetric creeping flow. Recently, collocation solutions were obtained for axisymmetric and nonaxisymmetric motion of a spherical particle between two parallel planes in Poiseuille and Couette flows, and in the case of sedimentation [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The derivatives of pressure can be expressed in terms of the derivatives of vorticity (6) Consider a coordinate transformation (7) defined as a solution of two elliptic quasilinear partial differential equations [9], (8) where (9) G is the Jacobian of the transformation (10) and P = P(ξ, η) and Q = Q(ξ, η) are functions chosen to control the spacing of coordinate lines in the x−y plane.…”
Section: Dimensionless Variables Are Introduced By the Relationships (3)mentioning
confidence: 99%
See 1 more Smart Citation